Family, nurse, and physician beliefs on family‐centered rounds: A 21‐site study. Issue 12 (21st September 2022) - Patel, Shilpa J.; Khan, Alisa; Bass, Ellen J.; Graham, Dionne; Baird, Jennifer; Anderson, Michele; Calaman, Sharon; Cray, Sharon; Destino, Lauren; Fegley, April; Goldstein, Jenna; Johnson, Tyler; et al.
Abstract: Background: Variation exists in family‐centered rounds (FCR). Objective: We sought to understand patient/family and clinician FCR beliefs/attitudes and practices to support implementation efforts. Designs, Settings and Participants: Patients/families and clinicians at 21 geographically diverse US community/academic pediatric teaching hospitals participated in a prospective cohort dissemination and implementation study. Intervention: We inquired about rounding beliefs/attitudes, practices, and demographics using a 26‐question survey coproduced with family/nurse/attending‐physician collaborators, informed by prior research and the Consolidated Framework for Implementation Research. Main Outcome and Measures: Out of 2578 individuals, 1647 (64%) responded to the survey; of these, 1313 respondents participated in FCR and were included in analyses (616 patients/families, 243 nurses, 285 resident physicians, and 169 attending physicians). Beliefs/attitudes regarding the importance of FCR elements varied by role, with resident physicians rating the importance of several FCR elements lower than others. For example, on adjusted multivariable analysis, attending physicians (odds ratio [OR] 3.0, 95% confidence interval [95% CI] 1.2–7.8) and nurses (OR 3.1, 95% CI 1.3–7.4) were much more likely than resident physicians to report family participation on rounds as very/extremely important. Clinician support for key FCR elements was higher than self‐reported practice (e.g., 88% believed family participation was important on rounds; 68% reported it often/always occurred). In practice, key elements of FCR were reported to often/always occur only 23%–70% of the time. Result: Support for nurse and family participation in FCR is high among clinicians but varies by role. Physicians, particularly resident physicians, endorse several FCR elements as less important than nurses and patients/families. The gap between attitudes and practice and between clinician types suggests that attitudinal, structural, and cultural barriers impede FCR.